The Power of Documentary Theatre to Promote Cross-National Understanding: Personal Impact of Performing With Their Voices Raised by Japanese and American Youth Actors - Liehr, Patricia; Matsuda, Yui; Ito, Mio; Morris, Kathryn; Nishimura, Chie; Takahashi, Ryutaro (Journal of holistic nursing, 2021)
The purpose of this article is to share descriptions of the personal impact for cross-national youth actors (Japanese, American) who performed ( ), a documentary theater script that shares the stories of Pearl Harbor and Hiroshima survivors who lived through the bombings of December 7, 1941, and August 6, 1945, respectively. This was a descriptive exploratory focus group study conducted immediately after student-actors from Funairi High School in Hiroshima ( = 15) and Farrington High School in Oahu, Hawaii ( = 8), performed . Data were content analyzed by a cross-national research team to address the question "What was the personal impact of performing for Japanese and American youth actors?" There were three themes that crossed national boundaries: sense of power of the message from real-life people, new cross-national awareness, and moving beyond familiar history to engage and learn. The fourth theme distinguished the youth groups: for Japanese youth, performing inspired an awareness of their local focus; for American youth, it enlivened youth-to-youth engagement as a learning approach. Documentary theater script is a creative, holistic approach with the potential to bridge divisiveness and promote cross-national understanding.